Short-time Work, Redundancies, and Changing Work Environment: The Hospitality Sector During COVID-19 - Rydell, Alexis; Storman, Elin (Nordic Journal of Working Life Studies, 2022)
This article focuses on the restructurings that took place within the hospitality sector during the economic downturn caused by the pandemic. The aim of this article is to examine how STW (short-time work) schemes and redundancies affected the psychosocial work environment. The data material consists primarily of 36 interviews with employees and managers from three hotels in Sweden that implemented STW schemes, where some employees were also made redundant. The results show that during the rather long period of government restrictions, radical shifts in hotel occupancy rates, and implemented STW schemes, the work environment changed in terms of employees’ perceptions of job (in)security; workload and work extension; time and financial structures; and workplace relations. Further, the results illustrate how hotel employees’ perceptions of the psychosocial work environment shifted over the course of the pandemic.